EXPLORING THE ROLE OF LOCUS OF CONTROL IN THE LAND ADMINISTRATION DELIVERY SERVICE - Farah Nabilah Mohammad Anuar; Noor Azniza Ishak; Nor A’tikah Mat Ali (Journal of Islamic, Social, Economics and Development, 2023)
Throughout the years, Malaysian land administration has been associated with a negative image for being slow and underperforming. To satisfy consumer demands, the land administration determined to improve the quality of land services. This article seeks to explore the role of locus of control in the land administration departments in Kedah. The methodology employed in this study is a combination of in-depth interviews and an online survey; or mixed methods. This study comprised 248 participants from the land administration departments in Kedah. In summary, the quantitative findings indicate that the majority of public servants have an external locus of control. The qualitative findings highlight five themes: (1) Decision-making, (2) Colleague Influence, (3) Training and Course, (4) Workload Issues, and (5) Reward and Promotion. In a nutshell, the role of locus of control among government employees in land administration departments is of the utmost importance to offer appropriate guidance for the implementation of courses or training designed to expand locus of control.